Analysis of 93 brain abscess cases to review the effect of intervention to determine the feasibility of the management protocol: A tertiary care perspective - Dhar, Sambuddha; Pal, Barnava (Asian Journal of Neurosurgery, 2021)
Context: Brain abscess is a suppurative process within the brain parenchyma, which remains a challenge for clinicians. Surgical excision or aspiration combined with prolonged antibiotics (usually 4–8 weeks) or only conservative management remains the treatment of choice. Aims: The purpose of this study is to analyze the epidemiology of brain abscess and to determine the potential factors leading to better outcomes. Settings and Design: This was a retrospective analysis of 93 patients undergoing various treatment options for brain abscess in a tertiary care center. Materials and Methods: Their preoperative status, etiology, and microbiological and clinical outcomes were analyzed. Statistical Analysis Used: Statistical analysis was done by Chi-square, one-way analysis of variance, and post hoc Newman–Keuls multiple comparison test wherever applicable using SPSS software. Results: Among 93 brain abscess cases, only 21 cases had a diameter <2.5 cm. Among them, conservative treatment was done for 38% of patients (8/21), aspiration for 47.6% (10/21) of patients, and excision for only 3 (14.2%) of cases. About 37.5% (3/8) persons among these conservatively managed patients had recurrence. None of the patients of <2.5 cm abscess having surgical management had recurrence or any new neurological deficits postsurgery during the 6-month follow-up. Conclusions: There was a significantly high recurrence among the nonsurgically treated patients with lesions <2.5 cm and there was no recurrence or neurological deficit after aspiration among these patients. Probably, aspiration has better results among these patients contrary to previous recommendations of antibiotic therapy alone.
Keywords: Abscess size; aspiration; brain abscess; craniotomy; recurrence